A wart or SCC? A case study and literature review of clinico-dermoscopic presentation in squamous cell carcinoma (SCC) - Sandhu, Jaspriya; Singh, Amandeep; Gupta, Sunil; Garg, Bhavna (Journal of Pakistan Association of Dermatologists, 2022)
Squamous cell carcinoma (SCC) is the second most common skin cancer, after basal cell carcinoma, in immunocompetent white individuals, and the most common skin cancer in immunosuppressed organ transplantation recipients worldwide. The diagnosis of SCC, although easily made in typical cases, may sometimes be difficult. Dermoscopy and histopathological examination help in diagnosis of SCC. Dermoscopy improves early diagnosis of skin cancer compared to the unaided eye. We report here a case of SCC presenting with an asymptomatic, warty growth on the shin for 1 year. Dermoscopic findings include yellowish hue with silvery white scaling and surface had few, irregularly arranged haemorrhagic dots. Histopathological examination showed features of SCC: nucleomegaly, pleomorphism, hyperchromasia & keratin pearl formation. A concise review of published literature has been presented of SCC cases reported with dermoscopic findings. We have here a case of moderately differentiated Squamous cell carcinoma of the shin; with an unusual history, clinical presentation and dermoscopic findings.